Síntese, propriedades estruturais e magnéticas dos óxidos ZnO e ZrO2 dopados com ferro - Souza, Antônio Oliveira de (2016)
The Zn1-x57FexO (0.0 x 0.10) and Zr1-xFexO2 (0.0 x 0.40) systems were synthesized, by freeze-drying and heat treatments, using as precursors of zinc and zirconium acetates (for lattice) and acetate enriched and natural iron (for doping). The heat treatments were conducted on the free atmosphere, at 400 and 600 °C for Zn1-x57FexO and Zr1-xFexO2, respectively, for 3 hours. The samples studied were characterized by thermogravimetry, differential scanning calorimetry (precursors), structural and magnetically by X-ray diffraction, scanning electron microscopy, magnetometry and Mössbauer spectroscopy. As a result of these analyzes, it was found that the iron solubility limit in hexagonal ZnO lattice is 5% at.. Lattice parameters and the average crystallite size of the solid solutions grow monotonically with increasing iron concentration and, above the threshold concentration, forming a spinel phase type ZnFe2O4. The Zn1-x57FexO system single phase presented a typical antiferromagnetic behavior at low and ferromagnetic at high temperatures to concentrations 3 and 5% at. Fe. While 1% at. Fe, showed spin glass properties at low and ferromagnetic at high temperatures. The results showed that the system Zr1-xFexO2 crystallized tetragonal structure zirconia low concentrations of iron and its cubic structure to intermediate concentrations, and that hematite is the secondary phase formed with higher levels of doping. The calculations showed that the lattice parameters of the solid solutions of zirconia decreases almost linearly with increasing dopant concentration. All single phase samples are paramagnetic at room temperature and low temperatures, with the exception of sample x = 0.25, which showed an incipient magnetization 13 K. In this case, there are antiferromagnetic fluctuations throughout the temperature range. In both systems the exchange interaction was assigned to two mechanisms occurring simultaneously: the interaction of direct exchange between magnetic moments near neighbors dominating at low temperatures and an interaction of indirect exchange-induced charge carriers with greater effectiveness high temperatures.